SLAM MISOOL: INTERNALIZATION OF ISLAMIC VALUES IN THE FRAME OF LOCAL CULTURE IN MISOOL ISLAND, RAJA AMPAT WEST PAPUA - Nur, indria; Tobroni; Ishomuddin (International Journal of Psychosocial Rehabilitation, 2026)
This article examines the internalization of Islamic values in the culture of Raja Ampat Misool Island. In addition to being known for being superior to its natural potential, Misool is also very thick with culture and traditions. Based on the results of the ethnographic method field research, the Misool community inherited Islamic values through a local culture which is routinely carried out every year for generations. Local culture and distinctive religious traditions on Misool Island are a means of transmitting Islamic teachings to the younger generation. Local culture and religious traditions such as Katilol, Sop Syafar, Tafu Kautun, Zikir, Ilayla, Dabus, and several other typical rituals for Islamic holiday celebrations are very synonymous with the value of belief (Aqidah), worship (ibadah) and morals (akhlak) either the morality to God (Allah) hablun min Allah, to among human (hablun min anNas), and to nature (hablun minal ’alam). Through existing Islamic values and supported by the values of local wisdom Fatanon (brotherhood, kinship) and Atnelevo (togetherness), deliver Islamic character to the Misool community who are obedient to God Almighty, establish good, harmonious and peaceful relationships with fellow citizens and maintain the ocean environment.